Multi-institutional dosimetric delivery assessment of intracranial stereotactic radiosurgery on different treatment platforms. (June 2020) - Dimitriadis, Alexis; Tsang, Yatman; Thomas, Russell A.S.; Palmer, Antony L.; Eaton, David; Lee, Jonathan; Patel, Rushil; Silvestre Patallo, Ileana; Gouldstone, Clare; Snaith, Julia A.D.; Kirkby, Karen J.; Nisbet, Andrew; et al.
Highlights: A multi-institutional end-to-end assessment of radiosurgery dosimetric delivery was performed for 33 plans in 30 participating centres using a variety of treatment platforms. The comparison has highlighted the dosimetric consistency achievable with different delivery platforms. The need for standardisation in intracranial stereotactic radiosurgery is highlighted. Abstract: Background and purpose: Assessment of dosimetric accuracy of radiosurgery on different treatment platforms. Material and methods: Thirty-three single fraction treatment plans were assessed at thirty centres using an anthropomorphic head phantom with target and brainstem structures. The target being a single irregular shaped target, ~8 cc, 10 mm from the brainstem. The phantom was "immobilised", scanned, planned and treated following the local protocols. EBT-XD films and alanine pellets were used to measure absolute dose, inside both the target and the brainstem, and compared with TPS predicted dose distributions. Results: PTV alanine measurements from gantry-based linacs showed a median percentage difference to the TPS of 0.65%. Cyberknife (CK) had the highest median difference of 2.3% in comparison to the other platforms. GammaKnife (GK) showed the smallest median of 0.3%. Similar trends were observed in the OAR with alanine measurements showing median percentage differences of1.1%, 2.0% and 0.4%, for gantry-based linacs, CK and GK respectively. All platforms showed comparable gamma passing rates between axial and sagittal films. Conclusions: This comparison has highlighted the dosimetric variation between measured and TPS calculated dose for each delivery platform. The results suggest that clinically acceptable agreement with the predicted dose distributions is achievable by all treatment delivery systems.